Does Climate Protest Work? Partisanship, Protest, and Sentiment Pools. (May 2020) - Bugden, Dylan
This study demonstrates whether and how climate protest increases or decreases the "sentiment pools" available to the climate movement. Using an experimental vignette survey design ( n = 1, 421), the author finds that compared with a control condition, peaceful marches are effective for both independents and Democrats, while civil disobedience has a positive effect among Democrats. These effects are isolated to those who are most certain of anthropogenic climate change. No effect is observed among Republicans. Despite evidence from other studies suggesting the possibility, no "backfire" effects are observed for any group or protest type. This study (1) lends supports to the use of tactical diversity within the climate movement and (2) demonstrates how the broader forces of partisanship interact with protest to shift the pool of supporters available to movements, extending our nascent collective knowledge of how partisanship shapes the outcomes of social movements and protest.